(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
This article provides a comprehensive comparison of the education systems of Finland and Uzbekistan, highlighting key features, approaches, and outcomes in each country. It explores Finland’s acclaimed education model, focusing on equity, teacher professionalism, and student-centered learning, while also examining Uzbekistan’s ongoing efforts to reform its education system, with an emphasis on access, curriculum adaptation, and vocational training. The annotation acknowledges the diverse challenges and approaches within each system and underscores the importance of drawing insights from global best practices to inform educational policies and practices worldwide